Regeneration capacity of cell suspension culture in Malaysian rice genotypes under salinity stress - Htwe, Nwe Nwe; Mahmood, Maziah; Ho, Chai Ling; Qamaruz Zaman, Faridah; Md Zain, Abdullah (Knowledgia Review, Malaysia, 2011)
Rice, a salt-sensitive species has a substantial genetic variation for salt tolerance within the cultivated gene pool. This study describes the establishment of cell suspension culture system and analysis of proline content of the selected rice genotypes under in vitro salt stress. The cell suspension cultures, initiated from the friable seed-derived callus, were established in MS medium supplemented with different concentrations of 2,4-D (0-25 μM) and subjected to different concentrations of NaCl (0-250 mM). The average Settled Cell Volume (SCV) of different clumps sizes was recorded. The results showed that MR219-4 exhibited the highest cell growth rate and regeneration capacity. The 750 μm sieved clumps have higher cell mass than the 500 and 250 μm sieved cell size. The shoot-regeneration capacity was maximum in 1/2 MS medium supplemented with 10 μM BAP. However, low regeneration capacity was obtained in NaCl treatments. MR219 (control) and MR219-9 appeared to be more NaCl tolerant than MR219-4. In addition, all genotypes significantly synthesized proline under NaCl conditions as demonstrated by the proline accumulation and MR219-4 revealed the lowest content among genotypes studied. These genotypes can be good model systems for studying the physiological mechanisms associated with in vitro selection for salt stress. This finding also suggests that proline may play a crucial role in protecting rice cells under salinity stress.